2012
DOI: 10.1007/s00774-012-0402-0
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in bone mineral density among older women

Abstract: The epidemiologic information regarding international differences in bone mineral density (BMD) in women is currently insufficient. We compared BMD in older women across five racial/ethnic groups in four countries. The femoral neck, total hip, and lumbar spine BMD were measured in women (aged 65–74 years) from the Study of Osteoporotic Fractures (SOF) (5,035 Caucasian women and 256 African American women in the US), the Tobago Women’s Health Study (116 Afro-Caribbean women), the Ms Os Hong Kong Study (794 Hong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
49
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 45 publications
7
49
1
2
Order By: Relevance
“…Our study showed that the BA group had greater BMD at all four sites compared with the AI group. In a comparison of BMD across four ethnic groups, Nam et al (38) attributed the greater BMD in African American women compared with Asian women to differences in weight. In our study, body weight was greater in the BA compared with AI females, largely due to greater lean mass.…”
Section: Discussionmentioning
confidence: 98%
“…Our study showed that the BA group had greater BMD at all four sites compared with the AI group. In a comparison of BMD across four ethnic groups, Nam et al (38) attributed the greater BMD in African American women compared with Asian women to differences in weight. In our study, body weight was greater in the BA compared with AI females, largely due to greater lean mass.…”
Section: Discussionmentioning
confidence: 98%
“…Potential reasons for this lack of association include differences in study methods and phenotype data, different genotyping methods and SNP genotype quality control, racial/ethnic differences in BMD, and insufficient sample size (Delezé et al 2000;Nam et al 2013;Wu et al 2013). Among other limitations, this study was based on a cross-sectional design, and the SNPs were selected from previous reports mainly in European populations.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral neck BMD in black men is 5.6 % higher than in Hispanic and 13.3 % than in white men [139]. The differences are greatly attenuated by an adjustment with body size [137,138].…”
Section: Racementioning
confidence: 95%
“…Many studies have shown that there exists substantial difference in BMD among different ethnic groups and even within a group of the same ethnic origin [135][136][137][138][139]. For example, black men have greater BMD than Hispanic or white men.…”
Section: Racementioning
confidence: 96%